Structural mechanics in forestry based on digital twin - Zarevich Anton; Poluektov Alexander; Sumina Yulya; Makarenko Philipp (BIO Web of Conferences)
Computational simulations are particularly relevant when it comes to robots operating in highly dynamic environments, such as robots used as mobile equipment in forestry. The structural design of such a robot is quite complex. However, this is usually done once at the beginning of the design process and the dynamic loads can only be estimated, leading to huge safety margins. In this paper, a digital twin approach to structural mechanics is proposed. Each feature of the environment (each tree, soil, etc.) as well as the robot itself can be represented by a digital twin. Rigid body dynamics are used to record all acting forces and impulses during the operation. These serve as input for finite element analysis, thus providing a holistic modelling framework.